Design, synthesis and structure activity relationships of indazole and indole derivatives as potent glucagon receptor antagonists. Issue 15 (1st August 2019) - Song, Fengbin; Xu, Guozhang; Gaul, Michael D.; Zhao, Baoping; Lu, Tianbao; Zhang, Rui; DesJarlais, Renee L.; DiLoreto, Karen; Huebert, Norman; Shook, Brian; Rentzeperis, Dennis; Santulli, Rosie; et al.
Graphical abstract: Abstract: A novel series of indazole/indole derivatives were discovered as glucagon receptor (GCGR) antagonists through scaffold hopping based on two literature leads: MK-0893 and LY-2409021. Further structure-activity relationship (SAR) exploration and optimization led to the discovery of multiple potent GCGR antagonists with excellent pharmacokinetic properties in mice and rats, including low systemic clearance, long elimination half-life, and good oral bioavailability. These potent GCGR antagonists could be used for potential treatment of type II diabetes.